Torghandlaren i Stockholm - Fundberg, Jesper (Tidsskrift for kulturforskning, 2006)
This article is based on fieldwork carried out among men working in a food and vegetable market in Stockholm. The focus is on oral and bodily practices in the market. My theoretical tools for the interpretations come from gender and post-colonial studies. Keywords are masculinities, practices, positions and situations. I have worked with and interviewed men to get their view of their encounters with people at the market. The examples in the article focus on male strategies and practices. The purpose of this study is to investigate how concepts such as gender, ethnicity, "white" and "black" masculinity are used and become relevant in these encounters.